THE PECULIARITIES OF SPEECH AND MUSIC INTERACTION IN SPEECH-AND-MUSIC WORKS - V. V. Marchenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article is devoted to revealing the peculiarities of speech and music integrated functioning in the generative process of a speech-and-music work. Various forms of speech and music interaction are presented, among which the simultaneous generation of speech and music component is regarded as the most productive while a speech-and-music product created by adding a musical component to the poetic text is considered to be the most controversial. In the paper the author dwells on the importance to understand what exactly helps the composer to feel the most essential points in such a complex unity that is a poetic text and to adequately convey the poet's original intention. Factors enabling adequate speech-and-music synthesis include the elements of intonation system, primarily rhythm and meter. Additionally, the nature of a speech-and-music work is predetermined by the means of lexical and syntactic language levels: The author stresses upon the special role of emotional-and-pragmatic potential, which accumulates the author's concept of a poetic text, conveyed with the help of the integrated interaction of all language means. The paper substantiates the expediency and feasibility of the further study of speech and music relations by the comparison of emotional-and-pragmatic potentials of a poetic and a speech-and-music work.